2020
DOI: 10.1016/j.jval.2020.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Centered Care for Women: Delphi Consensus on Evidence-Derived Recommendations

Abstract: Patient-centered care (PCC) could reduce gender inequities in quality of care. Little is known about how to implement patient-centered care for women (PCCW). We aimed to generate consensus recommendations for achieving PCCW.Methods: We used a 2-round Delphi technique. Panelists included 21 women of varied age, ethnicity, education, and urban/ rural residence; and 21 health professionals with PCC or women's health expertise. Panelists rated recommendations, derived from prior research and organized by a 6-domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 37 publications
0
19
0
1
Order By: Relevance
“…Our review identified a few studies of PCC among women, and those studies failed to fully conceptualize or describe PCC. We subsequently explored women's and clinicians' views about what constitutes PCC, 18 and generated recommendations by which to achieve PCC for women 19 …”
Section: Introductionmentioning
confidence: 99%
“…Our review identified a few studies of PCC among women, and those studies failed to fully conceptualize or describe PCC. We subsequently explored women's and clinicians' views about what constitutes PCC, 18 and generated recommendations by which to achieve PCC for women 19 …”
Section: Introductionmentioning
confidence: 99%
“…We mapped findings to a PCC framework as a means of thoroughly exploring elements of the health-care experience important to migrant women. 9,[18][19][20] In so doing, we further validated the Framework of PCC for Women and revealed key elements of PCC desired by migrant women. As a practical output, we generated 28 approaches that physicians can adopt to optimize PCC for migrant women.…”
Section: Study Strengths and Limitationsmentioning
confidence: 91%
“…We developed questions based on a comprehensive PCC framework that was rigorously developed by McCormack et al 9 with patients and clinicians, and then tailored based on interviews about PCC with diverse women who were largely Caucasian. [18][19][20] The Framework of PCC for Women is organized in six domains (foster a healing relationship, exchange information, address concerns, manage uncertainty, share decisions and enable self-care) and identifies strategies that clinicians can use to achieve each domain (File S1). We used a semistructured question guide (File S2) to understand whether migrant women experienced PCC according to its multidimensional components, and which domains were met or not met.…”
Section: Data Collectionmentioning
confidence: 99%
“…Durante los últimos años, la atención centrada en el paciente ha sido un foco intenso de los líderes de la atención sanitaria, así como un sinónimo de excelencia en la prestación de la atención (66) . Una de las innovaciones tiene en cuenta a la mujer, y la atención centrada en la mujer es considerada ahora parte de la atención sanitaria de las mujeres (67) . Sin embargo, los pacientes siguen teniendo poca influencia en los asuntos que más les afecta.…”
Section: Medicina Centrada En La Mujerunclassified